Study on interface bonding mechanisms for high-velocity oxygen-fuel spraying of WC-12Co coatings on AZ31B magnesium alloy - Xing Han; Chang Li; Xuan Wang; Haohao Mei (Journal of Materials Research and Technology)
As a lightweight structural material, Mg alloy is expected to have a broad application prospect. However, due to its poor wear resistance and corrosion resistance, its application range is greatly limited. In this paper, wear resistant and corrosion resistant coatings for WC-12Co were prepared on AZ31B substrate by HVOF thermal spraying. Considering the random probability distribution of particle size and the random distribution of substrate surface roughness under different sandblasting processes, the stochastic multi-particle deposition model was established based on the Coupling Euler Lagrange (CEL) method. The influence of substrate surface roughness on temperature field, stress field and strain field during coating formation was revealed. And the coating pores formation mechanism was revealed with experiments. The results show that the local stress at the bonding surface on the substrate is the largest. Centered on the bonding surface, the substrate internal stress decreases with the increase of the distance from the bonding surface. With the substrate surface roughness increasing, the coating internal residual stress slightly decreases. The local density changes caused by the particle spatial distribution randomness can produce stacking defects and then form pores. The substrate surface roughness has a small effect on the coating internal porosity.